Political activity of widows as an example of shaping cliental dependencies in the second half of the seventeenth and eighteenth centuries (Theatrum historiae, 2019)
Women played a significant role in the social life of old Poland. Widows, protected by privilegesand secured with property ownership, had a solid influence on the formation of cliental ties. Their role took on a dual character in this process, since they acted as both guardians of their clients and supplicants appealing to their own patrons for protection in pursuing or settling important matters for themselves, their relatives or family. The second half of the seventeenth and eighteenth centuries witnessed the ascent of a group of influential widows, who were eager to engage in state affairs, wanting to gain power and prestige for members of their family.
Keywords: patronage; clientelism; women’s patronage; customer relations; Polish-Lithuanian Commonwealth; 17th century; 18th century